Enhancing Financial Literacy and Digital Product Skills Through Canva for Sultan Iskandar Muda Students - Royanti Sinaga; Mahlian Elyana; M. Imam Santoso; Devi Purnama Sari (Penerbit Goodwood, 2026)
Purpose: This community service study aimed to enhance financial literacy and digital product development skills using Canva among Yayasan Perguruan Sultan Iskandar Muda (YPSIM) Senior and Vocational High School students. Research Methodology: The program employed a Participatory Action Research (PAR) and service-learning approach involving 31 students. Data were collected through pre- and post-test questionnaires, observations, and documentation of students’ digital products. Results: The average financial literacy score increased from 2.89 to 4.13, indicating an improved financial understanding. Students also produced digital products, including logos, labels, and promotional content, demonstrating their basic design competencies and entrepreneurial potential. Conclusions: Integrating financial literacy education with digital skills training effectively improves students’ financial awareness and creativity. Limitations: The program was limited to implementation in only one school, which restricts the generalizability of the findings to broader educational contexts. In addition, the relatively small sample size may not fully represent the diversity of student characteristics and learning conditions. The short implementation period also limited the ability to observe long-term impacts of the intervention on students’ financial literacy development and digital skill retention over time. Contributions: This study provides a practical model for integrating financial literacy and digital skills to enhance students’ competencies in supporting readiness for the digital economy.